Chronic effects of pitching on muscle thickness and strength of the scapular stabilizers in professional baseball players - Valle, O.; Sheridan, S. S.; Rauch, J. J.; Sarver, J. J.; Paul, R. W.; Thomas, S. J. (Sports Health: A Multidisciplinary Approach, 2023)
Background: The posterior scapular muscles eccentrically contract to disperse the high forces observed in the deceleration phase of pitching. Muscular adaptations often occur following chronic eccentric loading, however, no study has evaluated the adaptations of the posterior scapular muscles with regard to throwing and their relationship with humeral retroversion (HR) in professional pitchers.